Integrating Habitat Suitability and Larval Drift Modeling for Spawning‐To‐Nursery Functional Habitat Connectivity Analysis in Rivers - David Farò; Christian Wolter (Water Resources Research)
Abstract Habitat suitability modeling is a commonly used methodology to plan and assess in‐stream habitat enhancement in rivers, such as for the key fish life stages spawning and juvenile development. However, their use only allows modeling the spatial distribution of habitats, but not their connectivity. By integrating micro‐scale habitat modeling and a larval drift model, we assess the functional connectivity between spawning and larval nursery habitats for four rheophilic and litophilic fish species in a channelized and hydropower impacted reach of the lower Inn River (Bavaria, Germany), in which two restoration measures, a bypass channel and an island side‐channel system, have been constructed to improve longitudinal connectivity and habitat conditions. The study aims to (a) map spawning and larval nursery habitats, (b) quantify their connectivity, and (c) optimize functional habitat connectivity through an alternative bypass channel location. Results show that the channel's morphological complexity influences quantity and quality of available spawning and nursery habitats and their connectivity. Despite the presence of nursery habitats across the analyzed channel, the slow lateral larval dispersion during drift limits their accessibility to only the left river bank, making only 33% of available habitats useable. The degree of functional connectivity and hence the percentage of useable habitats can however be increased up to 95.3 % when considering different spatial configurations of habitats, which were explored in two alternative restoration scenarios. The results demonstrate the importance of considering functional habitat connectivity in habitat assessments and restoration planning.